PRACTICES MASTERING IN SOCIAL WORKERS' EDUCATIONAL TRAINING SYSTEM (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article devoted to the development of modern educational models of training in the field of "social work". Sets out the basic content, principles and methods of implementation of professionally oriented practices as a medium of personal maturity specialist.
Keywords: personal maturity; personal ability; professional practice-oriented professional tasks.